2006
DOI: 10.1007/s11250-006-4346-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anthelmintic resistance in nematode parasites of sheep and goats owned by smallholder farmers in eastern Ethiopia

Abstract: The anthelmintic resistance status was investigated of nematode parasites of sheep and goats owned by smallholder farmers in communities that received breeding stock from a source where a high level of anthelmintic resistance has been reported. The investigation used the faecal egg count reduction technique, whereby suitable animals within each of eight separate communities were pooled to achieve the numbers required to conduct separate tests for both sheep and goats. Anthelmintics tested were albendazole (ABZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 7 publications
3
12
4
Order By: Relevance
“…Our result also contrasts the previous report of Kumsa and Wossene (2006b) and Sissay et al (2006a) which is most probably due to the differences in the origin and management of the study animals as both previous studies were conducted in small ruminants kept under extensive management system owned by smallholder farmers. In contrast to the University farm under extensive management system, the level of drug selection on worm population is much lower owing to a majority of parasites being in refugia, and lower frequencies of treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result also contrasts the previous report of Kumsa and Wossene (2006b) and Sissay et al (2006a) which is most probably due to the differences in the origin and management of the study animals as both previous studies were conducted in small ruminants kept under extensive management system owned by smallholder farmers. In contrast to the University farm under extensive management system, the level of drug selection on worm population is much lower owing to a majority of parasites being in refugia, and lower frequencies of treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…both in the control group and pretreatment coprocultures from all groups supports the finding of the pre FECRT survey and is in agreement with report of Thomas et al (2007) and Sissay et al (2006a).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to WAAVP recommendations, an evidence of development of resistance in GINs, particularly H. contortus and Trichostrongylus spp., against OXF preparations was found. Previously, benzimidazole resistance against these worms have also been reported in goats (Chartier et al 1995(Chartier et al , 1998Sissay et al 2006;Cringoli et al 2007). …”
Section: Discussionmentioning
confidence: 91%
“…Because of the universal practice of communal grazing, it is of fundamental importance to attempt to achieve agreement amongst small-holders within each community who share common grazing pasture, to coordinate timing and method of treatment in their animals. It has been previously demonstrated that anthelmintic resistance is not present in nematode parasites of sheep and goat flocks owned by small-holder farmers in this region (Sissay et al 2006), therefore any broad-spectrum anthelmintic (provided it is from a reputable manufacturer) could be used. To obtain widespread compliance will not only require a concerted effort by livestock advisers in the area, but also provisions of regular and appropriate veterinary extension services (including subsidizing the cost of anthelmintic treatment) to the small-holder farmers in the region.…”
Section: Discussionmentioning
confidence: 99%